Open evaluation : integrating users into the selection of new product ideas - Haller, Jorg (Markt- und Unternehmensentwicklung / Markets and Organisations, 2013)
Selecting new product or service ideas that are worthwhile to be exploited has always been a major challenge to firms of all kinds. Recent developments, however, add a new facet to the evaluation challenge. Initiatives such as innovation contests, in which interested users may submit their ideas or solutions to firm relevant problems, frequently lead to several tens of thousands of submissions. Consequently, solutions are needed that help identifying the most promising ideas. Jörg Haller proposes a potential solution: open evaluation. Based on both qualitative and quantitative research, the author examines design options, strategies, and the capacity of open evaluation to efficiently and effectively support decision-making for innovation.   Contents: The Context of Open Evaluation: Innovation Contests The Design Elements and Objectives of Open Evaluation Key Factors affecting the Output of Open Evaluation The Capacity of Open Evaluation for Idea Selection How to Make the Crowd Your Jury   Target Groups: Researchers and students interested in the latest advances in research on open and user innovation Managers dealing with new product development, innovation management, and/or the design of information systems.   The Author: Dr. Jörg Haller received his PhD in economic sciences from the University of Erlangen-Nuernberg, where he worked as Research Associate for Prof. Dr. Kathrin M. Möslein at the Chair of Information Systems I.   The Editiors The series Markt- und Unternehmensentwicklung / Markets and Organisations is edited by Prof. Dr. Dres. h.c. Arnold Picot, Prof. Dr. Prof. h.c. Dr. h.c. Ralf Reichwald, Prof. Dr. Egon Franck and Prof. Dr. Kathrin M. Möslein.